2017
DOI: 10.1007/s10826-016-0650-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Contexts as Sources of Socialization: An Exploration of Intimate Partner Violence Experiences of Economically Disadvantaged African American Adolescents

Abstract: Intimate partner violence (IPV) among African Americans is a serious public health concern. Research suggest that African Americans adolescents, particularly those from economically disadvantaged communities, are at heightened risk for experiencing and perpetrating dating violence compared to youth from other racial and ethnic groups. In the present study, we examined different relationship contexts that are sources of IPV socialization. Semi-structured interviews were conducted with 22 economically disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Corroborating this result, a survey carried out in the city of Brasília, Brazil, with first-year high school students from a public school, revealed that adolescents recognize the end of relationships as a way of coping with violence in affectivesexual relationships, violence and resignation (20) . Regarding the response to violence through aggression, this fact was also evidenced in a study developed with economically disadvantaged African American adolescents, which revealed the presence of IPV reciprocity among adolescents (21) .…”
Section: Discussionmentioning
confidence: 71%
“…Corroborating this result, a survey carried out in the city of Brasília, Brazil, with first-year high school students from a public school, revealed that adolescents recognize the end of relationships as a way of coping with violence in affectivesexual relationships, violence and resignation (20) . Regarding the response to violence through aggression, this fact was also evidenced in a study developed with economically disadvantaged African American adolescents, which revealed the presence of IPV reciprocity among adolescents (21) .…”
Section: Discussionmentioning
confidence: 71%
“…As stated earlier, the prevalence of dating violence among teens from African American households is higher in comparison with other racial groups (Henry & Zeytinoglu, ). Additionally, given the high proportion of low‐income families in the sample, there is increased concern that minority teens in rural areas who live in families with limited resources are especially vulnerable to dating violence (Landor et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of high school students in the United States revealed that non-Hispanic Black students reported the highest proportion of physical dating violence victimization in the past 12 months (Kann et al, 2018). Additional studies found that younger African Americans from economically disadvantaged backgrounds are at disproportionate risk for experiencing dating violence, both as perpetrators and as victims (Henry & Zeytinoglu, 2012;Landor et al, 2017).…”
Section: Teen Involvement In Violent Dating Relationshipsmentioning
confidence: 99%
“…For instance, Glass and Few-Demo (2013) used symbolic interactionism and Black feminist theory to explore the support groups of Black lesbian couples and show how interactions with family and friends influenced how couples assigned meaning and reacted to cultural scripts about their racial and sexual identities. Symbolic interactionism has also been demonstrated with other outcomes such as academic achievement, intimate partner violence, and delinquency (Giordano, Copp, Manning, & Longmore, 2013; Giordano, Phelps, Manning, & Longmore, 2008; Landor et al, 2016; Lonardo, Giordano, Longmore, & Manning, 2009). Thus, consistent with this theory, we focus on the level of relationship quality and comfort communicating about sex as central to understanding sexual health outcomes within self-reported monogamous, sexual relationships of young adult women.…”
Section: Symbolic Interactionist Frameworkmentioning
confidence: 99%